Inhibiting the DNA damage response pathway promotes functional recovery after spinal cord injury - Zubair Ahmed; Richard I. Tuxworth (Wiley, 2022)
Abstract Spinal cord injury (SCI) affects up to 1.26 million people every year, leading to permanent disability and death. The biggest causes of SCI are motor vehicle accidents, falls and interpersonal violence with clinical outcomes very much dependent on the severity and location of the lesion. Frequently, there is loss of motor or sensory function below the level of injury. At present, there are no restorative treatments for SCI patients, with only palliative treatments on offer and complicated further by the low intrinsic capacity of the central nervous system to regenerate. A recent study by Tuxworth and Ahmed, published in Clinical and Translational Medicine1 shows that inhibiting ataxia‐telangiectasia mutated (ATM) kinase, a central regulator of the DNA damage response pathway, promoted axon regeneration and remarkable improvements in sensory and motor function after SCI in both mice and rats. Moreover, the ATM inhibitor, AZD1390, is potent and highly selective, orally bioavailable and brain‐penetrant.2 AZD1390 is currently being developed for the treatment of brain cancers but with its simple route of administration (oral), has the potential to be re‐purposed for use in SCI.